2017
DOI: 10.1093/jrr/rrx026
|View full text |Cite
|
Sign up to set email alerts
|

Differences in responses to X-ray exposure between osteoclast and osteoblast cells

Abstract: Radiation-induced bone loss is a potential health concern for cancer patients undergoing radiotherapy. Enhanced bone resorption by osteoclasts and decreased bone formation by osteoblasts were thought to be the main reasons. In this study, we showed that both pre-differentiating and differentiating osteoclasts were relatively sensitive to X-rays compared with osteoblasts. X-rays decreased cell viability to a greater degree in RAW264.7 cells and in differentiating cells than than in osteoblastic MC3T3-E1 cells. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 47 publications
(66 reference statements)
4
29
0
3
Order By: Relevance
“…In this study, we investigated the formation of multinucleated osteoclast cells after γ irradiation at a range of doses between 0.1 and 1 Gy in RAW 264.7 cells. Analysis of survival of the cells indicated a typical dose response, consistent with the reported study showing that these cells are radiosensitive [ 35 ]. The cell concentration after 1 Gy γ irradiation was about 60% of the non-irradiated samples after a 5-day culture.…”
Section: Discussionsupporting
confidence: 87%
“…In this study, we investigated the formation of multinucleated osteoclast cells after γ irradiation at a range of doses between 0.1 and 1 Gy in RAW 264.7 cells. Analysis of survival of the cells indicated a typical dose response, consistent with the reported study showing that these cells are radiosensitive [ 35 ]. The cell concentration after 1 Gy γ irradiation was about 60% of the non-irradiated samples after a 5-day culture.…”
Section: Discussionsupporting
confidence: 87%
“…In addition, X-rays, applied as a whole body irradiation of 2 Gy in mice, lead to an increase in osteoclastic differentiation and bone resorption, which is determined by increasing OC numbers and surface area, as well as increasing serum markers of bone resorption [ 58 ]. The differential effects of IR on OCs may depend on the applied dose of IR, as Zhang et al found that low doses of X-rays promoted osteoclastogenesis, whereas high doses led to the reduced differentiation of OCs, probably by the induction of apoptosis and actin disorganization [ 26 ]. As high doses of IR induce a damage response and inflammatory processes in affected tissues such as bone, the secretion of pro-inflammatory cytokines, e.g., tumor necrosis factor (TNF) α, interleukin (IL) -6 and IL-1 may be stimulated.…”
Section: High Dose Radiation—ir In Cancer Therapy and The Influencmentioning
confidence: 99%
“…As all other tissues and cells, bone and the associated bone remodeling cells are also prone to radiation-induced damage. The effects of radiation on bone-associated cell types are especially important in questions of the medical application of IR, as well as for questions on environmental radiation effects [ 19 , 20 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…As radiation effects are known to vary for different bone cell types and locations 30,34,35 , we assessed the four sub-volumes separately (Table 2). The applied micro-CT protocol did not significantly affect bone formation and resorption activities in the callus VOIs (DC, DP and FP) from week 5-6 with similar bone volume observed in week 5 and 6 for controls and scanned animals.…”
Section: Resultsmentioning
confidence: 99%
“…So far only few studies have focused on the underlying mechanisms of radiation-induced effects on bone mainly focusing on changes in expression profiles of osteoblast and osteoclast differentiation markers 30,35 . Recently, three consecutive in vivo studies by Chandra et al 36,53,54 showed, that radiation‐induced bone loss 53,54 is mediated via Sclerostin inhibition of osteoanabolic Wnt-signaling 36 .…”
Section: Discussionmentioning
confidence: 99%